3D‐printed design of a stereotaxic adaptor for the precision targeting of brain structures in infant mice. (31st January 2022) - Steffens, Simon; Bakker, Joanne; Glat, Micaela; Keimpema, Erik; Pollak, Daniela D.; Hökfelt, Tomas; Harkany, Tibor
Abstract: Experimental investigation of early postnatal brain development in infant mice (<postnatal day 10) is challenging because of the rapid expansion of their brain volume and the fragility of cranial bones. Stereotaxic adaptors that are commercially available usually evoke significant compression forces, thus limiting the accuracy of micromanipulations. Here, we took advantage of recent progress in 3D printing for the cost‐effective production of stereotaxic adaptors for infant mice. Our designs offer gentle head positioning, tailored incisor placement and high precision, while also integrating evaporator and tubing components for gaseous anaesthesia. Thus, post‐procedural lethality is minimized even upon time‐consuming surgeries. Viral microinjections through glass capillaries are shown as proof of principle to experimentally validate targeting accuracy in mice aged 6–10 days. The exact engineering workflow and printing protocol are disseminated for open‐label use. Overall, we present technical details and experimental data on a stereotaxic device that can help neurobiologists working at a particularly complex developmental stage in mice. Abstract : Experimental investigation of early postnatal brain development in infant mice is challenging because of the rapid expansion of their brain volume and the fragility of cranial bones. Here, we offer 3D‐printed stereotaxic adaptors for infant mice. Our designs offer gentle head positioning and tailored incisor placement, while also integrating evaporator and tubing components for gaseous anaesthesia.